2003
DOI: 10.1007/s11664-003-0200-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth of GaN on porous SiC and GaN substrates

Abstract: GaN films were grown on porous SiC and GaN templates using both plasma-assisted molecular beam epitaxy (PAMBE) and metal-organic chemical vapor deposition (MOCVD) to evaluate possible advantage of epitaxy on a porous substrate. For the growth of GaN on porous SiC by PAMBE, transmission electron microscopy (TEM) observations indicate that the exposed SiC suface pores tend to extend into the GaN film as open tubes and to trap Ga droplets. The GaN layers grown on porous templates have fewer threading dislocations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…Since the year 2000, there have been quite a number of reports on epitaxial growth of GaN on porous silicon carbide (PSC) substrates with various degrees of open porosity at the surface [6][7][8][9][10]. It has been demonstrated that GaN films grown on PSC were strain relaxed as compared to those grown on non-porous SiC.…”
Section: Introductionmentioning
confidence: 99%
“…Since the year 2000, there have been quite a number of reports on epitaxial growth of GaN on porous silicon carbide (PSC) substrates with various degrees of open porosity at the surface [6][7][8][9][10]. It has been demonstrated that GaN films grown on PSC were strain relaxed as compared to those grown on non-porous SiC.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Although porous GaN offers a good alternate to grow high quality stress free over layer, yet very little work has been done. Recently, few studies on the bandgap and morphology control in porous GaN through electroless wet chemical and photoelectrochemical etching are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Many possible application scenarios, such as the layer transfer method or epitaxial growth of GaN [4], require the deposition of thin films via CVD without filling the porous material. This could in principle be shown with a sample having a resistivity of 0.106 Ω·cm, as is illustrated in Figure 3.…”
Section: Discussionmentioning
confidence: 99%